2018
DOI: 10.3389/fpubh.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Contextual Nutrition Education Manual Enhanced Nutrition Teaching Skill

Abstract: Background: A theory-based contextual nutrition education manual (NEM) may enhance effective teaching of nutrition in schools. School nutrition education should lead to the realization of such benefits as improved health, scholarly achievement leading to manpower development and consequently the nation's development. The purpose of the study was to develop a contextual NEM for teachers of Grade 5 and 6 learners in the Bronkhorstspruit district, South Africa, and to assess teachers' perception on the use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The ineffectiveness of the intervention can be associated with the absence of an underlying theory of behavioral change. Studies have suggested that effective interventions that are theory-based provide opportunities for participants to learn and practice skills through interactive teaching, role play, videos, play competition and demonstration aimed at changing their behavioral practice [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The ineffectiveness of the intervention can be associated with the absence of an underlying theory of behavioral change. Studies have suggested that effective interventions that are theory-based provide opportunities for participants to learn and practice skills through interactive teaching, role play, videos, play competition and demonstration aimed at changing their behavioral practice [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers developed a set of nutrition education materials, comprising a teacher's manual, picture book, learner's workbooks, and posters (29). Selected constructs of the Social cognitive theory (SCT) (30) and the Meaningful learning model (MLM) (31), in combination with the results of a prior needs assessment (3234), were used to explain the nutrition topics in the existing curriculum of the DoBE.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the family plays a crucial role in determining a child's eating habits due to the child's tendency to imitate the older members of the family. As far as the school environment is concerned, the greatest influence is exerted by teachers, who act as role models, promoting or discouraging a particular health behavior (Kupolati et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%